Enalaprilat and losartan decrease erythroid precursors frequency in cells from patients with polycythemia vera - Angela Bozza; Martina Bernardi; Daniela Catanzaro; Katia Chieregato; Anna Merlo; Giuseppe Astori (Hematology, 2023)
ABSTRACTObjective: Polycythemia Vera (PV) is a myeloproliferative neoplasm characterized by the overproduction of red blood cells. First-line therapies are directed at lowering hematocrit levels. After the discovery of a mutation in the Janus kinase 2 (JAK2V617F), JAK2 inhibitors have been tested as second-line therapies. Despite these approaches, there is still the need for a major comprehension of the mechanisms involved in PV erythrocytosis and of more effective therapies. Angiotensin-converting enzyme (ACE) stimulates hematopoietic precursors proliferation and erythroid differentiation. We thus hypothesized that ACE inhibition could help in controlling erythrocytosis in PV.Methods: We assessed the clonogenic potential by colony-forming unit (CFU) assay of mononuclear cells isolated from PV JAK2 positive or JAK2 negative patients with erythrocytosis treated with enalaprilat or losartan.Results: Treatment with drugs led to a decrease of erythroid precursor frequency both in the presence and absence of JAK2 mutation, with a high extent in JAK2 positive cells and without affecting other types of precursors. No dose-dependent effect was observed.Conclusions: Our results demonstrate that ACE inhibition reduces erythroid precursor frequency, confirming the involvement of ACE in erythrocytosis despite the presence of JAK2 mutation and encouraging the hypothesis that ACE inhibitors and AT1R antagonists could help in directly managing erythrocytosis in PV.